Establishing an Electrophysiological Recording Platform for Epidural Spinal Cord Stimulation in Neuropathic Pain Rats - Yang CT; Shyu BC; Lin WT; Lu KH; Lin CR; Wen YR; Chen CC (Journal of Pain Research)
Chin-Tsang Yang,1– 3 Bai-Chuang Shyu,1 Wei-Tso Lin,4 Kuo-Hsiang Lu,4 Chung-Ren Lin,5 Yeong-Ray Wen,6– 8,* Chih-Cheng Chen1,9,10,* 1Institute of Biomedical Sciences, Academia Sinica, Taipei, Taiwan; 2Department of Leisure Industry and Health Promotion, National Ilan University, Yilan, Taiwan; 3Department of Biotechnology and Animal Sciences, National Ilan University, Yilan, Taiwan; 4Gimer Medical Co., New Taipei City, Taiwan; 5Department of Anesthesiology, National Cheng Kung University Hospital, Tainan, Taiwan; 6Pain Management and Research Center, Department of Anesthesiology, China Medical University Hospital, Taichung, Taiwan; 7Chun Chuan Orthopedic and Pain Specialty Hospital, Taichung, Taiwan; 8Pain Management Center, Department of Anesthesiology, Jen-Ai General Hospital, Taichung, Taiwan; 9Neuroscience Program of Academia Sinica, Academia Sinica, Taipei, Taiwan; 10Taiwan Mouse Clinic, Biomedical Translational Research Center, Academia Sinica, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Chih-Cheng Chen; Yeong-Ray Wen, Email chih@ibms.sinica.edu.tw; yray.wen@gmail.comPurpose: Spinal cord stimulation (SCS) is pivotal in treating chronic intractable pain. To elucidate the mechanism of action among conventional and current novel types of SCSs, a stable and reliable electrophysiology model in the consensus animals to mimic human SCS treatment is essential. We have recently developed a new in vivo implantable pulsed-ultrahigh-frequency (pUHF) SCS platform for conducting behavioral and electrophysiological studies in rats. However, some technical details were not fully understood. This study comprehensively analyzed methodology and technical challenges and pitfalls encountered during the development and implementation of this model.Materials and Methods: Employing a newly developed pUHF-SCS (± 3 V, 2 Hz pulses with 500-kHz biphasic radiofrequency sinewaves), we assessed analgesic effect and changes of evoked local field potentials (eLFPs) in the bilateral primary somatosensory and anterior cingulate cortices in the rats with or without spared nerve injury (SNI) using the platform. The placement of stimulating needle electrodes in the hind paw was examined and optimized for functionality.Results: SNI enhanced the C component of eLFPs in bilateral cortexes elicited by stimulating the contralateral but not the ipsilateral lateral aspect of the hind paw. Repeated pUHF-SCS significantly reversed SNI-induced paw hypersensitivity and reduced C-component enhancement. An impedance test can determine an optimal SCS electrode function: an SCS discharge threshold of 100– 400 μA for cortical activation or a motor threshold of 150– 600 μA for the hind limbs. Impedance increased due to growth of fibrotic tissue but stabilized after post-implantation day 12.Conclusion: We presented a reliable electrophysiological platform for SCS application in rat neuropathic pain model and demonstrated potent analgesic effects of pUHF-SCS. All device implantations or pUHF-SCS per se did not cause evident spinal cord damage. This safe and stable platform provides an in vivo rat model for SCS investigation of mechanisms of action and device innovation.Keywords: spinal cord stimulation, pulsed-ultrahigh-frequency, evoked local field potential, primary somatosensory cortex, anterior cingulate cortex